Pressure effects on the structural, elastic , electronic and optical properties of ZnO from first-principles calculations - LAKEL, Said; ELHAMRA, F.; IBRIR, M. (Science des matériaux (Laboratoire LARHYSS), 2015)
First-principles calculations of the structural, electronic, optical and elastic properties of ZnO as a function of the pressure have been performed within density functional theory using Ultra soft pseudo potentials and generalized gradient approximation (GGA) for the exchange and correlation energy. Through our results, we note that the lattice constants decrease with the pressure increasing. Also, the elastic constants C 11 , C 12 , C 13 and C 33 and  the bulk modulus B increase with the pressure increasing. However, the elastic constants C 44 , the Shear modulus ( G ) and  Young’s modulus ( E ) decrease slowly with  increasing pressure, the band gap increases with the pressure increasing and ZnO has direct band. As pressure increases, the static dielectric constants ɛ 1 (0) and static refraction index n(0) decrease. Our calculated results are in good agreement with experimental data and other theoretical calculations. Keywords : DFT calculation, electronic, optical, elastic, under pressure